The Role of Transparency and Accountability in Mediating the Influence of Digital Technology Utilisation on Muzakki Trust (A Study of BAZNAS in Malang City) - Azizah Nur Hidayah Azizah; Eko Suprayitno; Nihayatu Aslamatis Solekah (Prodi Manajemen Zakat dan Wakaf, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Langsa, 2026)
Abstract (English version) Objective – This study aims to analyse the role of transparency and accountability in mediating the influence of digital technology utilisation on muzakki trust. and to determine the influence between independent and dependent variables. Methodology – This study employs a quantitative approach by surveying 120 muzakki of BAZNAS in Malang City, who were selected using purposive sampling based on specific criteria, namely active contributors who have experience with zakat payment services. Data were collected through structured questionnaires designed to measure the relationships among the research variables. The sample size is considered adequate for analysis using Partial Least Squares–Structural Equation Modelling (PLS-SEM), which is applied to examine the significance of relationships between variables. The data were processed using SmartPLS version 4. Research Results – The findings indicate that digital technology has a significant impact on transparency and accountability. However, transparency does not have a significant impact on trust nor does it act as a mediator between the use of digital technology and trust, whereas accountability has a significant impact and serves as the primary mediator in the relationship between the use of digital technology and the trust of donors. Limitations – This study has limitations in terms of the relatively small number of research subjects, with the area covered being only one region and one institution. Practical Implications – As a practical implication, the results of this study contribute to Enhancing the integration of digital systems that not only focus on transaction services but also include the publication of audit reports and the distribution of funds in real time. Building digital literacy regarding zakat for Muzakki, so that the public understands the mechanisms and security of the digital zakat system, thereby increasing public trust. Strengthening internal accountability mechanisms, including Sharia audits and annual reports that are easily accessible online, to maintain the credibility of the zakat institution. Originality/value - This study advances the literature on digital zakat governance by demonstrating that accountability, rather than transparency, serves as the primary mediating mechanism through which digital technology utilization enhances muzakki trust. Abstrak (versi bahasa) Tujuan – Penelitian ini bertujuan untuk menganalisis peran transparansi dan akuntabilitas dalam memediasi pengaruh pemanfaatan teknologi digital terhadap kepercayaan muzakki, dan untuk menentukan pengaruh antara variabel independen dan dependen. Metodologi – Penelitian ini menggunakan pendekatan kuantitatif dengan mensurvei 120 muzakki BAZNAS di Kota Malang, yang dipilih menggunakan purposive sampling berdasarkan kriteria tertentu, yaitu kontributor aktif yang memiliki pengalaman dengan layanan pembayaran zakat. Data dikumpulkan melalui kuesioner terstruktur yang dirancang untuk mengukur hubungan antar variabel penelitian. Ukuran sampel dianggap memadai untuk analisis menggunakan Partial Least Squares–Structural Equation Modelling (PLS-SEM), yang diterapkan untuk menguji signifikansi hubungan antar variabel. Data diolah menggunakan SmartPLS versi 4. Hasil Penelitian – Temuan menunjukkan bahwa teknologi digital memiliki dampak signifikan terhadap transparansi dan akuntabilitas. Namun, transparansi tidak memiliki dampak signifikan terhadap kepercayaan, juga tidak bertindak sebagai mediator antara penggunaan teknologi digital dan kepercayaan, sedangkan akuntabilitas memiliki dampak signifikan dan berfungsi sebagai mediator utama dalam hubungan antara penggunaan teknologi digital dan kepercayaan para donatur. Keterbatasan – Studi ini memiliki keterbatasan dalam hal jumlah subjek penelitian yang relatif kecil, dengan area yang dicakup hanya satu wilayah dan satu lembaga. Implikasi Praktis – Sebagai implikasi praktis, hasil studi ini berkontribusi pada: Meningkatkan integrasi sistem digital yang tidak hanya berfokus pada layanan transaksi tetapi juga mencakup publikasi laporan audit dan distribusi dana secara real time. Membangun literasi digital mengenai zakat bagi Muzakki, sehingga masyarakat memahami mekanisme dan keamanan sistem zakat digital, sehingga meningkatkan kepercayaan masyarakat. Memperkuat mekanisme akuntabilitas internal, termasuk audit Syariah dan laporan tahunan yang mudah diakses secara online, untuk menjaga kredibilitas lembaga zakat. Orisinalitas/nilai - Studi ini menawarkan perspektif baru mengenai tata kelola zakat digital dengan menunjukkan bahwa akuntabilitas merupakan jalur mediasi yang lebih efektif dibandingkan transparansi dalam mengubah pemanfaatan teknologi digital menjadi kepercayaan muzakki.